The Biochemical Outcome of two Treatment Protocols in Patients With Opium-associated Lead Poisoning: A Cross-sectional Study in North of Iran - Badsar, Alireza; Gholami, Zeynab; Rahbar Taramsari, Morteza; Atrkar Roshan, Zahra; Mohammadi Kojidi, Hamid; Aghajany Nasab, Monireh (International Journal of Medical Toxicology and Forensic Medicine, 2021)
Background: Lead is a potent toxin that targets heme synthesis and some antioxidant enzymes that induce oxidative stress. Lead exposure remains one of the significant health concerns all over the world. Chelating agents have been used as antidotes for acute and chronic lead poisoning. The present study was conducted to evaluate the biochemical outcome of two different chelating therapies. Methods: This descriptive cross-sectional study was performed in the Razi University Hospital, Rasht, Guilan. Fifty-six patients with a history of opium use were enrolled in the study who were treated symptomatically. Blood lead Llevels (BLL), Hemoglobin (Hb), Red Blood Cell (RBC), White Blood Cell (WBC), urea, creatinine, Alanine aminotransferase (ALT), Aspartate aminotransferase (AST), and Alkaline Phosphatase (ALP) were evaluated before and after treatment. The BLL more than 100μg/dl with clinical symptoms was considered as severe lead poisoning (n=34) who received 4 days of DMPS (2,3-dimercaptopropane-1-sulfonate) injection. Other cases with BLL of 20-100μg/dl were considered as those with mild poisoning (n=22) that were treated with oral D-Penicillamine for 14 days. Results: The mean age of patients was 49.73±14.11 years. Data analysis indicated no significant differences between the groups at baseline regarding the demographic variables. A significant reduction was observed in BLL before and after the intervention using the D-Penicillamine from 75.88±26.22 to 44.3±17.51 μg/dl (P=0.0001). The BLL reduced from 105.5±34.04 to 24.51±24.08 μg/dl after treatment with DMSP (P=0.0001). The levels of ALT, AST, and WBC significantly decreased post-treatment following using D-penicillamine and DMPS (P<0.05). The D-Penicillamine-treated group showed an increase in Hb and RBC (P<0.05). Conclusion: According to the results, penicillamine improves low to moderate lead toxicity. Although DMSP decreases BLL significantly and reverses liver enzymes, further investigations on Hb and RBC, are needed.